The survival of the Greek gods in early Christianity - Le Roux, M. (Journal for semitics, 2007)
From what we know of the historical sources, the Hellenistic period in the ancient Near East (more specifically ancient Israel), can be divided into four uneven phases. The first was the conquest of Palestine by Alexander the Great’s armies and the ensuing wars of succession (332-296 BC). The second and more important phase was the rule of the Egyptian Ptolemaic dynasty in 296-201 BC. This phase was followed by the Seleucids of Syria, who also ruled the country for approximately 100 years (200-104 BC) and the fourth and last phase of the Hellenistic period, which at the ancient Semitic city of Dor, lasted just forty years but has left almost no record, was the period of Hasmonean domination of the northern coastal region in 104-64/3. The excavations at Tel Dor and many other sites in Israel contribute substantially to our knowledge of the history of the cities and of the region in general, and are particularly important for understanding the final stages in the transformation of many cities in Israel into fully Greek cities. The Semitic people were heavily influenced by Greek culture. All the religious artefacts - clay figurines, stone statues, and incense altars - are taken from the Greco-Roman pantheon. The ancient Near East offered a suitable environment where various religious beliefs expressed in many artistic forms were interwoven. Christianity came into being in Palestine, a province of the Greco-Roman Empire. By 400 AD the Catholic Church was largely identified with the Roman state. What influence did the different religions like Greco/Roman religion have on ancient Israel and eventually Christianity? Were they swept away, or were they raised to a new level (Wessels 1994:14)? What changes did the newly-brought, translated Christian faith undergo under the influence of these cultures and religions? How did Christianity and Christian faith combine with pre-Christian culture and religion?,